Keefektifan Implementasi Pembelajaran Berdiferensiasi pada Mata Pelajaran IPAS Kelas V SD Supriyadi Semarang - Alfina Choirun Nadwah; Muhammad Prayito (Journal on Education, 2024)
Differentiated learning is an effort or process to adapt the learning system in the classroom to the different learning needs and abilities of each student. Students have their own learning styles and learning needs. As an educator, you must be able to be a facilitator in every learning process so that students' interests can be met and educational goals can be achieved efficiently. Based on the results of observations and questions and answers with Mrs. Naili as the class teacher at VD Supriyadi Elementary School, information was obtained that the characteristics of class VD students were different and in the science and science subject, the material on students' magnetic properties did not meet the KKM. This research aims to explain that efficient differentiated education can improve student learning outcomes. The method used by researchers in this research is a quantitative method. The research concept used is One Group Pretest- Posttest Design. The information analysis method uses the N-Gain experiment. Based on the results of the N-gain experiment, generally the N-gain Percent is 77, 74 with a minimum of 45 and a maximum of 100. The results of the paired samples test sig. (2-tailed) of 0.000 < 0.005 can be concluded that there is an important comparison between the practice results from the pretest and posttest. This shows that differentiated learning is effectively used for science and science learning for Class V students at SD Supriyadi Semarang.